2019
DOI: 10.1128/jvi.00786-19
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA Lnc-MxA Inhibits Beta Interferon Transcription by Forming RNA-DNA Triplexes at Its Promoter

Abstract: Previously, we identified a set of long noncoding RNAs (lncRNAs) that were differentially expressed in influenza A virus (IAV)-infected cells. In this study, we focused on lnc-MxA, which is upregulated during IAV infection. We found that the overexpression of lnc-MxA facilitates the replication of IAV, while the knockdown of lnc-MxA inhibits viral replication. Further studies demonstrated that lnc-MxA is an interferon-stimulated gene. However, lnc-MxA inhibits the Sendai virus (SeV)- and IAV-induced activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 47 publications
2
48
0
Order By: Relevance
“…LYAR interacts specifically with the N-terminal domain of activated IRF3 and in this way interferes with the DNA-binding capacity of IRF3 in the IRF3-CBP/p300 holocomplex. Additionally, a long non-coding RNA directly targets the IFNβ promoter region and interferes with transcription factor binding in a unique way [ 165 ]: After RNA deep sequencing revealed enhanced transcription of the long non-coding RNA lnc-MxA from the MxA locus after viral infection, Li and colleagues recently reported its mechanism of action. Applying a chromatin isolation by RNA purification assay and in vitro pulldown of an IFNβ promoter dsDNA fragment with biotin-labelled lnc-MxA, they demonstrated that lnc-MxA forms an RNA-DNA triplex with the IFNβ promoter region.…”
Section: All In Moderation—the Many Ways To Adjust Irf3 Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…LYAR interacts specifically with the N-terminal domain of activated IRF3 and in this way interferes with the DNA-binding capacity of IRF3 in the IRF3-CBP/p300 holocomplex. Additionally, a long non-coding RNA directly targets the IFNβ promoter region and interferes with transcription factor binding in a unique way [ 165 ]: After RNA deep sequencing revealed enhanced transcription of the long non-coding RNA lnc-MxA from the MxA locus after viral infection, Li and colleagues recently reported its mechanism of action. Applying a chromatin isolation by RNA purification assay and in vitro pulldown of an IFNβ promoter dsDNA fragment with biotin-labelled lnc-MxA, they demonstrated that lnc-MxA forms an RNA-DNA triplex with the IFNβ promoter region.…”
Section: All In Moderation—the Many Ways To Adjust Irf3 Activitymentioning
confidence: 99%
“…Applying a chromatin isolation by RNA purification assay and in vitro pulldown of an IFNβ promoter dsDNA fragment with biotin-labelled lnc-MxA, they demonstrated that lnc-MxA forms an RNA-DNA triplex with the IFNβ promoter region. This changes the structure of the chromatin and interferes with binding of the transcription factors IRF3 and NF-κB to their respective target sequence [ 165 ]. Finally, the delayed generation of PRDI-binding factor 1 (PRDI-BF1, or PR/SET domain 1) mediates recruitment of the histone H3 lysine methyltransferase G9a for epigenetic silencing of IFNB1 expression [ 166 , 167 ].…”
Section: All In Moderation—the Many Ways To Adjust Irf3 Activitymentioning
confidence: 99%
“…Influenza virus FM1-infected pneumonia leads to an inflammatory storm, suggesting that many pro-inflammatory cytokines like TNF-α and IL-6 released into blood and lung tissue [28][29][30]. In our study, FM1 was non-invasive intratracheally instilled into lung tissue of mice.…”
Section: Anemoside B4 Decreases Fm1-induced Cytokines Release In Serummentioning
confidence: 66%
“…In turn, lnc-Lsm3b (lncRNA U6 snRNA-associated Sm-like protein) is an IFN-induced lncRNA that blocks the shift in the conformation of RIG-I, required for signaling, limiting IFNβ production [89]. Acting downstream, lnc-MxA (lncRNA Interferon-induced GTP-binding protein MxA) is also an IFN-induced lncRNA that interferes with IFNβ transcription by forming a DNA-RNA triplex helix at the IFNβ promoter [90]. Therefore, lnc-Lsm3b and lnc-MxA are IFN-induced lncRNAs that help viral replication.…”
Section: Ifn-related Lncrnasmentioning
confidence: 99%